ANALISIS PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA MAKERUH KECAMATAN RUPAT KABUPATEN BENGKALIS - Welasari, Welasari; Ardieansyah, Ardieansyah (UIR PRESS, 2016)
Community participation in village development is needed to progress and develop a village . Development has the nature and purpose of the public welfare , as well as village development aimed at the welfare of the villagers . Community participation in rural development by providing community contribute ideas in decision making , contribution of labor to the activities of mutual cooperation, to contribute funds to non-governmental and maintain development results . Successful development with community participation.